ORGANIZATIONAL AND ECONOMIC MECHANISMS FOR IMPLEMENTING THE CLUSTER APPROACH IN THE MANAGEMENT OF VOCATIONAL EDUCATION INSTITUTIONS (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
The contemporary landscape of vocational education and training (VET) is characterized by a widening gap between the competencies generated by educational institutions and the dynamic skill requirements of the modern labor market. This article addresses the systemic inefficiencies of traditional, centralized management models and proposes the "Cluster Approach" as a strategic mechanism for organizational and economic transformation. By integrating educational providers, industrial enterprises, and regional governance bodies into a unified ecosystem, the cluster model aims to optimize resource allocation, diversify funding streams, and enhance the employability of graduates. The first part of this study critically analyzes the theoretical underpinnings of educational-industrial clusters, drawing upon Michael Porter’s competitive advantage theory and the "Triple Helix" model of innovation. It establishes the conceptual framework for shifting from a supply-driven education system to a demand-driven, network-based governance structure essential for sustainable regional economic development.